SERVICE OF MOORING, PILOTAGE, AND TUGGING IN SUPPORTING THE SMOOTH OPERATION OF SHIPS AT TANJUNG EMAS SEMARANG PORT - MUHAMMAD IDRIS; Agus Sulistiono (JURNAL VENUS, 2026)
This study aims to analyze the effectiveness of pilotage, towage, and mooring services at Tanjung Emas Port Semarang, as well as the factors influencing the effectiveness of these three services. The findings indicate that pilotage services at Tanjung Emas Port take an average of 1.5 hours, which is longer than the expected standard time. The longer pilotage time is due to limited pilot personnel and insufficient pilot vessel capacity to handle large ships. Towage services also significantly affect the waiting time of ships, with an average towage delay of 1-2 hours, which is longer than the desired standard. The limited towage vessel capacity and lack of coordination between towage officers hinder the efficiency of towage services. Mooring services, especially at the lower berth of the Samudera dock, are affected by extreme weather conditions, such as rob, which leads to delays in mooring ships. The factors affecting the effectiveness of these three services include limitations in human resource capacity, vessel capacity (towage and pilot vessels), and weather impacts, which can delay service processes. The multiple linear regression model used in this study shows that pilotage, towage, and mooring services collectively explain 69.2% of the variation in port effectiveness. Therefore, towage vessel capacity, pilot personnel, and mooring infrastructure that can withstand adverse weather conditions are key factors that need to be addressed to improve port operational effectiveness.